2015
DOI: 10.5152/balkanmedj.2015.15619
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Alpha Lipoic Acid on Rat Sciatic Nerve Ischemia Reperfusion Damage

Abstract: Background: Alpha lipoic acid is a potent antioxidant that plays numerous roles in human health. This study examined the effect of ALA on rat sciatic nerve ischemia reperfusion damage. Aims: Protective effect of alpha lipoic acid (ALA) on sciatic nerve following ischemia-reperfusion in rats was investigated by using light microscopy and biochemical methods. Provided that the protective effect of ALA on sciatic nerve is proven, we think the damage to the sciatic nerve that has already occurred or might occur in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…In addition, Skibska and Goraca [8], reported that thioredoxin (Trx), a redox signaling molecule similar to HO-1 and Nrf2, which are highly regulated during oxidative stress (hypoxia), is upregulated in ALA-treated rats and indirectly activates antioxidant expression. Our results are also in agreement with those of Turamanlar and colleagues [27], who reported that in rats with sciatic nerve ischemic injury the elevated MDA, SOD, GSH peroxidase, and GSH levels revert to normal in response to ALA. Oxidative stress and inflammation are interlinked responses. The levels of nuclear factor NF-p65 and pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-6 were greatly augmented in the HI group.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, Skibska and Goraca [8], reported that thioredoxin (Trx), a redox signaling molecule similar to HO-1 and Nrf2, which are highly regulated during oxidative stress (hypoxia), is upregulated in ALA-treated rats and indirectly activates antioxidant expression. Our results are also in agreement with those of Turamanlar and colleagues [27], who reported that in rats with sciatic nerve ischemic injury the elevated MDA, SOD, GSH peroxidase, and GSH levels revert to normal in response to ALA. Oxidative stress and inflammation are interlinked responses. The levels of nuclear factor NF-p65 and pro-inflammatory cytokines such as TNF-α, IL-1β, and IL-6 were greatly augmented in the HI group.…”
Section: Discussionsupporting
confidence: 94%
“…Similar experimental studies based on oxidative stress models also demonstrated decreased SOD level with ALA treatment. [34,35] Turamanlar et al [31] also constituted ischemia-reperfusion damage on rat sciatic nerve and showed increased levels of GPx with addition of ALA in treatment group. Consistent with the literature, our study validated that levels of all above mentioned antioxidant enzymes decreased with ischemia-reperfusion and significantly increased with preconditioning with ALA in the treatment group, with the exception of GPx levels, in which the increase was not statistically significant.…”
Section: Discussionmentioning
confidence: 97%
“…As activity and level of CAT enzymes are low in the brain tissue, GPx is the prior enzyme that detoxificates hydrogen peroxide in the neural tissue. [31,32] Senoglu et al [33] showed in their study that the decline in the tissue SOD activity after sciatic nerve damage was reversed with ALA treatment. Similar experimental studies based on oxidative stress models also demonstrated decreased SOD level with ALA treatment.…”
Section: Discussionmentioning
confidence: 98%
“…NO is produced by iNOS and can lead to HIR injury. These data revealed that LA reduced the formation of excess NO generated by reperfusion through the decrease in iNOS mRNA expression, and reduced cell damage caused by NOS superoxide and peroxynitrite anion formed by NO (Turamanlar et al 2015, Patrick 2006.…”
Section: Vol 68mentioning
confidence: 94%
“…MIP-2 is a potent neutrophil chemokine, which is a member of the chemokines C-X-C families (Xue et al 2011, Tao et al 2014. MIP-2 is an important chemokine, has a dual role in the body: on the one hand, the specificity of chemotaxis of neutrophils to tissue inflammation, strengthen the clearance of neutrophils to pathogens, Vol.…”
Section: Effect Of La On Mip-2mrna and Inos Mrna In Liver Tissue Aftementioning
confidence: 99%